Purpose-built accommodations: what attributes do students value more when choosing where to live? - Giannella, Marcela Gomes (2018)
This research reveals what attributes and services student housings and purpose-built accommodations provide their target groups with. It analyzes not only the developing and growing student housing market in Brazil but also its trends with the goal of establishing which characteristics students from four specific private institutions (FGV-Eaesp, FAAP, Mackenzie and PUC) value more when choosing their accommodation. By studying what is a student housing and offered attributes, analyzing benchmarks, competitors and market tendencies, one was able to gather information that allowed to define what aspects are considered a priority during a renting decision making process. The qualitative and quantitative field researches enhanced the analysis by distinguishing what is of basic provision and what adds value to the business as well. The expected result of this study is to provide the real estate company which will develop the purpose-built residency for students with their target group profile and preferences, linking the findings from the carried research to the academic information on the subject and the market assessment of the sector.